Hra Flaška: Dětské formalizované hry - stabilnost formy a proměnlivost leitmotivu - Bittnerová, Dana (Lidé města, 2001)
Game is one of the cornerstones of children's social communication. Children select a game with a view to the social context, character and objectives of communication. They select it either from a fixed game repertory or they update the repertory by adopting new game schemes, innovating old games or inventing new games. The children's flexible approach to the content of a game, while keeping its form, is evidenced in the paper with the use of the example of the game Flaška (Bottle). Transformations of its content were examined in the active game repertory of schoolchildren from an elementary school class in Prague during five years (1996-2000). The rules according to which the children played Flaška in the second, fourth, fifth and sixth classes are based on the same concept. During the game campaign children gathered at one of the banks in a class during the pause. Here, any of the children, but usually a socially strong, highly respected, schoolboy, twirled a bottle from a beverage. The one who was targeted by the neck of the bottle acquired a special position. This designation depended on the concrete leitmotiv for which children in the individual classes played. In the second class the leitmotiv was to simulate marginalisation of a member of one's own group, while two years later it was an examination of mutual affection between boys and girls. In the fifth class the game measured the schoolchildren's courage in the sphere of sexual display and violation of taboo. At the end of the sixth class the game mediated direct physical contact of boys and girls. At the children's higher age the originally boyish (isosexual) game could not exist without a mixed (heterosexual) audience. A microanalysis of the game Bottle has described one aspect of the working and transmission of cultural phenomena in culture in general. The search for a new leitmotiv or internal meaning in established forms is one of the aspects of culture, an aspect ensuring not only its continuity, but also reproduction.